Phytochemical screening, antimicrobial and antioxidant studies of Lannea egregia Engl. and K. Krause (Anacardiaceae) stem bark - Basirat O. Rafiu; Adeola M. Sonibare; Enitan O. Adesanya (AOSIS, 2019)
Background: A substantial number of drugs are being developed from plants for the treatment of various diseases. Lannea egregia (LE) is a woody perennial plant used traditionally in the management of skin disorders and wounds. Aim: To investigate the biological activities of different solvent extracts of LE bark. Settings: Fresh stem bark of Lannea egregia was collected from Itabo Lanlate, Oyo State, Nigeria. The authentication was done in Forest Herbarium, Ibadan (FHI), Nigeria. The biological activities of the air-dried sample were carried out in the Department of Pharmacognosy, University of Ibadan, Nigeria. Materials and methods: Powdered LE bark sample was extracted by gradient extraction. Phytochemical screening was performed on the extracts using standard procedure. In vitro antimicrobial study was performed on 14 strains of bacteria and 5 fungal strains at a concentration range of 25, 50, 75 and 100 mg/mL of the extract using ciprofloxacin and itraconazole as standard. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were determined. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and total phenolic content (TPC) of two active extracts were determined spectrophotometrically. Results: The phytochemical screening of LE revealed the presence of tannins, terpenoids, flavonoids, anthraquinones, saponins and alkaloids. The dichloromethane (DCM) extract exhibited the highest activity against all the bacterial strains as well as four of the fungal strains. The zones of inhibition (ZI) of bacteria ranged from 9.0 ± 2.0 to 24.6 ± 2.4 mm, MIC of 0.0008 to 12.5 mg/mL and MBC of 25 to 75 mg/mL, while ZI of the fungal strains ranged from 10.3 ± 4.6 to 18.0 ± 5.3 mm, MIC 0.391 - 0.781 and MFC of 50 mg/mL in all the strains. The TPC values of DCM and ethyl acetate (EtOAc) extracts were 1582.47 ± 6.69 and 1579.89 ± 12.77 µg GAE/mg and inhibitory antioxidant activity of 2.54 ± 0.58 and 2.44 ± 0.54, respectively. Conclusion: These findings provide scientific evidence to support the ethnomedicinal use of Lannea egregia bark for treating skin disorders and wounds.